Structural analysis of vibration platform for panel units forming and consideration of its utilizing options - Nazarenko, Ivan; Diachenko, Oleksandr; Pryhotskyi, Vasyl; Nesterenko, Mykola (Academic journal Industrial Machine Building Civil Engineering, 2021)
The review of the utilizing directions of the shakers of various designs for consolidation of concrete mixtures at the production of flat panel elements is executed. The major limitations and advantages of certain designs of shakers are analyzed, the main production technologies of flat reinforced concrete units in which their use is most reasonable. The evaluation of prospects for the equipment of different designs to be quickly adjusted to the production program changes is made. The main idea in the production of flat panel elements on vibrating pads using Industry 4.0 technologies is to use the latest information technology and automation and that business and engineering processes are deeply integrated.
Keywords: readjustment; pallet; vibration platform; technology; volume consolidation